The Ideas Differences Between Soekarno and Hatta’s Regarding The National Movement Strategy In 1927-1936 - Novita Ayu Karisma; Kayan Swastika; Sumardi Sumardi (JURNAL HISTORICA, 2018)
Ethical political in Indonesia brings the effect on the appearance of modern organization.Modern organization has a leader who was very influential with the method of struggle toindependence day that was Soekarno and Hatta. But, there was different way in a struggleleading organization. The pupose of this research were: (1) to study the background/factors that make a difference about struggle strategy of Soekarno and Hatta toward theindependence of indonesia in the national movement era, (2) to study the thought aboutstrategy struggle of Soekarno and Hatta toward independence of Indonesia in an era of thenational movement and (3) to study the impact of the difference thought about strategystruggle of Soekarno and Hatta toward independence of Indonesia to whole of the nationalmovement. A theory that used in this research were a theory hermeneutika and sociologyknowledge approach. The methods used in this research were heuristic, critic,interpretation, and historiography. The result of this research were: the concept ofSoekarno struggle in the era of the national movement was mass-action, while concept ofHatta struggle in the era of the national movement was education cadresKeywords: thought, Soekarno, Hatta, national movement and struggle strategy